Anti-methicillin-resistant Staphylococcus aureus activity and safety evaluation of 14-O-[(5-ethoxycarbonyl-4,6-dimethylpyrimidine-2-yl) thioacetyl] mutilin (EDT) - Yuhang Zhou; Yunpeng Yi; Jing Yang; Hongjuan Zhang; Qinqin Liu; Shengyi Wang; Wanxia Pu; Ruofeng Shang (Scientific Reports, 2023)
Abstract Infections caused by methicillin-resistant Staphylococcus aureus (MRSA) have threated the public health worldwide, which emphasizes the urgent need for new drugs with novel mechanism of actions. 14-O-[(5-ethoxycarbonyl-4,6-dimethylpyrimidine-2-yl) thioacetyl] mutilin (EDT) is a pleuromutilin compound with high activity against several Gram-positive bacteria in vitro and in vivo. This study aimed to verifying the potential anti-MRSA activity and evaluating the safety of EDT. In in vitro antibacterial activity assays, EDT exhibited potent antibacterial activity against MRSA isolated from clinic (minimum inhibitory concentration = 0.0313–0.125 μg/mL), increased post-antibiotic effect (PAE) values and limited potential for the development of resistance. Docking model and green fluorescent protein (GFP) inhibition assay further elucidated the higher antibacterial activities of EDT via mechanism of action. In safety evaluation, EDT exhibited low cytotoxic effect and acute oral toxicity in mice and avoided to significantly increase the number of revertant colonies of six tested strains in the Ames study. Furthermore, EDT displayed a moderate inhibitory effect on CYP3A4 and moderate stability in mouse and human liver microsomes, providing a promising agent for the development of new antimicrobial candidate.